PENGARUH DISCOVERY LEARNING DAN YOUTUBE TERHADAP KEMAMPUAN MENULIS CERPEN SISWA KELAS IX SMPN 4 SUKABUMI - Eva Oktavia Dewi Putri; Hera Wahdah Humaira; Deden Ahmad Supendi (Universitas Negeri Makassar, 2023)
This study aims to describe the use of discovery learning and YouTube on the ability to write short stories in class IX SMPN 4 Kota Sukabumi. This study used an experimental method with a one-group pretest-posttest research design. The sample in this study was 26 students, using the purposive sampling technique. The data collection technique was in the form of an essay test that was conducted twice, namely a pretest and a posttest. Based on the results of the analysis, there are several problems that cause students to have difficulty writing short story texts, namely difficulty developing ideas from the given theme, lack of vocabulary mastery, lack of student motivation in writing, and the use of learning models and media that are given less creatively. The results showed that the average score of students when doing the pretest was 53.31, which increased to 76.38 in the posttest results. The calculation results of the test were obtained using the t-test, obtained a t_hitung value of 15.072 and a sig value (2-tailed) of 0.00. Thus, the sig value (2-tailed) <0.05 which indicates that there is a significant difference between the pretest and posttest. Thus, it can be concluded that the use of the discovery learning model and youtube has an effect on the ability of students in class IX SMP Negeri 4 Kota Sukabumi to write short stories.